Efficacy and Safety of an Investigational Single-Course CRISPR Base-Editing Therapy Targeting PCSK9 in Nonhuman Primate and Mouse Models. Issue 3 (31st October 2022) - Lee, Richard G.; Mazzola, Anne Marie; Braun, Maurine C.; Platt, Colin; Vafai, Scott B.; Kathiresan, Sekar; Rohde, Ellen; Bellinger, Andrew M.; Khera, Amit V.
Abstract : Background: VERVE-101 is an investigational in vivo CRISPR base-editing medicine designed to alter a single DNA base in the PCSK9 gene, permanently turn off hepatic protein production, and thereby durably lower low-density lipoprotein cholesterol. We test the efficacy, durability, tolerability, and potential for germline editing of VERVE-101 in studies of nonhuman primates and a murine F1 progeny study. Methods: Cynomolgus monkeys were given a single intravenous infusion of a vehicle control (n=10) or VERVE-101 at a dose of 0.75 mg/kg (n=4) or 1.5 mg/kg (n=22) with subsequent follow-up up to 476 days. Two studies assessed the potential for germline editing, including sequencing sperm samples from sexually mature male nonhuman primates treated with VERVE-101 and genotyping offspring from female mice treated with the murine surrogate of VERVE-101 (VERVE-101mu). Results: Liver biopsies 14 days after dosing noted mean PCSK9 editing of 46% and 70% in monkeys treated with VERVE-101 at 0.75 and 1.5 mg/kg, respectively. This translated into mean reductions in blood PCSK9 (proprotein convertase subtilisin/kexin type 9) of 67% and 83% and reductions of low-density lipoprotein cholesterol of 49% and 69% at the 0.75 and 1.5 mg/kg doses, respectively, assessed as time-weighted average change from baseline between day 28 and up to 476 days after dosing. Liver safety monitoring noted a transient rise in alanine aminotransferase and aspartate aminotransferase concentrations after infusion that fully resolved by day 14 with no accompanying change in total bilirubin. In a subset of monkeys necropsied 1 year after dosing, no findings related to VERVE-101 were identified on macroscopic and histopathologic assessment of the liver and other organs. In the study to assess potential germline editing of male nonhuman primates, sperm samples collected after VERVE-101 dosing showed no evidence of PCSK9 editing. Among 436 offspring of female mice treated with a saturating dose of VERVE-101mu, the PCSK9 edit was transmitted in 0 of 436 animals. Conclusions: VERVE-101 was well tolerated in nonhuman primates and led to 83% lower blood PCSK9 protein and 69% lower low-density lipoprotein cholesterol with durable effects up to 476 days after dosing. These results have supported the initiation of a first-in-human clinical trial in patients with heterozygous familial hypercholesterolemia and atherosclerotic cardiovascular disease.